Teacher Quality Dimensions in Improving the Quality of National Education at Madrasah Aliyah in Lampung - Dacholfani, Muhammad Ihsan; Wibowo, Agus; Fadillah, Muhammad Kharis (Madania: Jurnal Kajian Keislaman, 2022)
This article explores the development of teacher quality dimensions in improving the quality of national education. Methods This research uses a case study with a mixed methods approach. The sampling technique uses a random sampling technique with respondents. Based on the findings in this study, the results of the analysis were obtained with a Satorra-Bentler Scaled Chi-Square value of 189.190 and a p-value coefficient of 0.070 > 0.05, RMSEA of 0.030 <0.080, CFI ≥ 0.90, so the model obtained is "good fit" (acceptable model suitability) then the dimensions in the professional management of teachers in improving the quality of education are the three dimensions of learning which include lesson preparation, implementation, and evaluation. In addition, the results of the information obtained by students expect quality teachers such as having preparation, knowledge/ability in teaching, class management, personality, dedication, open-mindedness, responsibility, varied teaching methods, punctual work, and good judgment. This research suggests that if changes in the education system need to be developed, policy recommendations prioritize teacher staff and the determinants of teacher effectiveness. Artikel ini bertujuan untuk mendalami perkembangan dimensi kualitas guru dalam meningkatkan mutu pendidikan nasional. Metode Penelitian ini menggunakan studi kasus dengan pendekatan mix methods. Teknik sampling menggunakan teknik random sampling dengan responden. Berdasarkan temuan pada penelitian ini diperoleh hasil analisis dengan nilai Satorra-Bentler Scaled Chi-Square sebesar 189,190 dan koefisien p value sebesar 0,070 > 0,05, RMSEA sebesar 0,030 < 0,080, CFI ≥ 0,90 maka model yang diperoleh adalah “good fit” (kecocokan model dapat diterima). Oleh sebab itu, dimensi dalam pengelolaan profesional guru dalam meningkatkan kualitas pendidikan yaitu pada tiga dimensi pembelajaran yang meliputi persiapan pembelajaran, implementasi dan evaluasi. Selain itu, hasil informasi yang diperoleh siswa mengharapkan guru yang berkualitas seperti memiliki persiapan, pengetahuan/ kemampuan dalam mengajar, manajemen kelas, berkepribadian, berdedikasi, berpikiran terbuka, bertanggung jawab, metode pengajaran yang bervariasi, tepat waktu dalam bekerja serta melakukan penilaian yang baik. Saran penelitian ini yaitu jika perubahan sistem pendidikan perlu dikembangkan maka rekomendasi kebijakan mengedepankan tenaga guru dan faktor penentu efektivitas guru.